Public archaeology and geophysics: searching for unmarked human burials in rural Colorado - Rowe, Donald J., author; Henry, Edward, advisor; Harry, Dennis, committee member; LaBelle, Jason, committee member (Colorado State University. Libraries, 2023)
Rural communities in Colorado are often left in control of lands that potentially contain unmarked burials. Two such communities in Colorado, Gould and Wray, are interested in examining the possible existence of unmarked burials on public lands. The land near the Gould Community Center was used to house prisoners of war during the final year of World War 2 and the community believes mostly fallen concrete markers (one still stands) found at the site may be related to burials from that time. Wray, CO in Yuma County is home of the East Yuma County Cemetery Board (EYCCB), which manages the Kingston and Evangelical Lutheran Cemeteries. The EYCCB took over management of these properties after periods of abandonment and the burial records are lost, this has the left them with potential unmarked burials at each of these sites. The expense and ethical concerns related to accidental disinterment provide rural communities an incentive to locate any unmarked burials on land they manage. I combined four geophysical methods with historical information provided by community partners to determine what areas at the respective sites were most likely to contain unmarked burials. The four methods I employed include: ground-penetrating radar (GPR), electrical resistivity tomography (ERT), electromagnetic induction (EMI), and magnetometry. Using these methods, I was able to locate numerous geophysical anomalies and geolocate them in the mapping software of ArcGIS Pro. In Gould I was unable to determine the source of the geophysical anomalies found due to the wide variety of uses the site has had in the past as well as the lack of historical evidence for burials. Historical evidence of previous burials at the Kingston and Evangelical Lutheran Cemeteries allowed me to make the argument that these anomalies were potentially related to burials. At Evangelical Lutheran Cemetery I concluded the cemetery is likely to contain unmarked burials throughout the southern half of the site. However, the lack of geophysical markers suggests that the soil in the northern quarter of the site is largely undisturbed and likely does not have burials. I concluded that Kingston Cemetery is expected to contain burials in the south and west of the site. Additionally, the part of Kingston Cemetery that is least likely to contain unmarked burials is the northeastern corner of the site, with a strip along the northern boundary that possibly contains burials.
Keywords: electromagnetic induction; historic cemetery; electric resistivity tomography; magnetometry; ground penetrating radar